American High School Students' Knowledge and Beliefs about Parenting and Early Childhood Development - Eleanor O'Donnell Weber; Joseph Clark McIntyre; Meredith L. Rowe (MDPI AG, 2022)
Income-based achievement gaps in cognitive skills are already large when children enter Kindergarten. By adopting a preventative approach that considers the efficacy of providing parenting knowledge to individuals before they become parents while they are still in secondary school, we may be able to reduce achievement gaps. In this study, we examined adolescents' knowledge and understanding of parenting and child development by creating and validating the Adolescent Parenting Knowledge and Attitudes Survey and administering it to over 1000 US high school students. This study shows that while many high school students hold beliefs consistent with successful outcomes for young children and their learning, there is much room for increasing their knowledge. The findings are discussed as presenting a potential opportunity to use high school as a site to improve adolescents' knowledge and attitudes related to child rearing and development.